2022
DOI: 10.1007/s12671-021-01822-2
|View full text |Cite
|
Sign up to set email alerts
|

Compassion Protects Mental Health and Social Safeness During the COVID-19 Pandemic Across 21 Countries

Abstract: Objectives The COVID-19 pandemic is having an unprecedented detrimental impact on mental health in people around the world. It is important therefore to explore factors that may buffer or accentuate the risk of mental health problems in this context. Given that compassion has numerous benefits for mental health, emotion regulation, and social relationships, this study examines the buffering effects of different flows of compassion (for self, for others, from others) against the impact of perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 88 publications
9
41
0
1
Order By: Relevance
“…In the current study, this hypothesis was supported with all three flows of fears of compassion predicting psychological distress (depression, anxiety and stress) and social safeness. This is consistent with previous findings that compassion as a multidimensional construct predicts psychological distress (Kirby et al, 2019) and social safeness (Kelly & Dupasquier, 2016) and is in accordance with a related study examining the flows of compassion in relation to COVID-19 (Matos, McEwan, et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the current study, this hypothesis was supported with all three flows of fears of compassion predicting psychological distress (depression, anxiety and stress) and social safeness. This is consistent with previous findings that compassion as a multidimensional construct predicts psychological distress (Kirby et al, 2019) and social safeness (Kelly & Dupasquier, 2016) and is in accordance with a related study examining the flows of compassion in relation to COVID-19 (Matos, McEwan, et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…This finding may again be related to the notion that during the COVID-19 pandemic, others have become threats, fuelling fears of contraction, and therefore inhibiting compassion involving contact with others, either receiving compassion from others or offering compassion to others, resulting in increased anxiety. This is consistent with findings from the related study (Matos, McEwan, et al, 2021) which found compassion for others did not moderate the relationship, and previous findings which have generally found that fears of compassion for others has less impact on psychological distress (Kirby et al, 2019).…”
Section: Fear Of Compassion For Otherssupporting
confidence: 92%
See 3 more Smart Citations